The Use of Chemical Flocculants and Chitosan as a Pre-Concentration Step in the Harvesting Process of Three Native Microalgae Species from the Canary Islands Cultivated Outdoors at the Pilot Scale - Laura Figueira Garcia; Zivan Gojkovic; Marianna Venuleo; Flavio Guidi; Eduardo Portillo (Microorganisms)
Biomass harvesting represents one of the main bottlenecks in microalgae large-scale production. Solid–liquid separation of the biomass accounts for 30% of the total production costs, which can be reduced by the use of flocculants as a pre-concentration step in the downstream process. The natural polymer chitosan and the two chemical flocculants FeCl3 and AlCl3 were tested on freshwater Chlorella sorokiniana and two marine algae, Dunaliella tertiolecta and Tetraselmis striata. A preliminary screening at the laboratory scale was performed to detect the most suitable doses of flocculants. On the basis of these results, selected doses were tested on the pilot scale, using the flocculants for a pre-concentration step and the centrifugation as a second step to confirm the effectiveness of flocculants in a realistic operational environment. The biomass recoveries (Rpilot, %) of 100 L cultures were as follows: (1) for T. striata, Rpilot = 94.6% for 0.08 g/L AlCl3, 88.4% for 0.1 g/L FeCl3, and 68.3% for 0.04 g/L chitosan; (2) for D. tertiolecta, Rpilot = 81.7% for 0.1 g/L AlCl3, 87.9% for 0.2 g/L FeCl3, and 81.6% for 0.1 g/L chitosan; and (3) for C. sorokiniana, Rpilot = 89.6% for 0.1 g/L AlCl3, 98.6% for 0.2 g/L FeCl3, and 68.3% for 0.1 g/L chitosan. Flocculation reduced the harvesting costs by 85.9 ± 4.5% using chemical flocculants. Excesses of aluminum and iron in the biomass could be solved by decreasing the pH in the biomass combined with washing. This is the first study, to the best of our knowledge, that investigates the pilot-scale flocculation of three native Canarian microalgal strains. A pilot-scale pre-concentration step before centrifugation can improve the yield and reduce costs in the microalgae harvesting process.